Semiologia dekodowania wiedzy w organizacjach sieciowych - Cieśliński, Wojciech B. (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article presents semiology as an instrument of identification and description of knowledge within the area of virtual network organizations. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 75-84